Drug Management in Increasing Immigrant Patient Satisfaction through Service Quality at Dr. Wahidin Sudirohusodo Hospital Makassar - Abdelrazig Babiker Ahmed; Faradiba Abdul Rasyid; Ahmad Najib (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Patient satisfaction is a key indicator in assessing the quality of healthcare services, especially for immigrant patients who face language, cultural, and information access challenges. This study aimed to analyze the influence of medication management and service quality on immigrant patient satisfaction at Dr. Wahidin Sudirohusodo General Hospital in Makassar. The study employed a quantitative approach with a causal design, involving 60 immigrant subjects selected through purposive sampling. Data collection was conducted via questionnaires and direct interviews, then analyzed using the Partial Least Square (PLS) method. The results indicated that medication management has a positive and significant effect on immigrant patient satisfaction (β = 0.319; p < 0.05), while service quality demonstrates a stronger and more significant influence (β = 0.668; p < 0.001). The R² value of 0.953 indicates that both variables can explain 95.3% of the variation in patient satisfaction. Service quality dimensions including reliability, responsiveness, assurance, empathy, and tangibles played an important role in enhancing satisfaction. These findings emphasized the importance of culturally sensitive medication management and quality service in shaping positive experiences for immigrant patients and improving the overall effectiveness of healthcare services.